Green Economy Transition in Nepal: Environmental Kuznets Curve Analysis - Gyan Mani Adhikari; Rajendra Adhikari; Rajesh Keshar Khanal (Journal of Development and Administrative Studies, 2025)
This study examines the relationship between economic growth and environmental degradation in Nepal through the lens of the Environmental Kuznets Curve (EKC) hypothesis, with particular focus on the country's green economy transition initiatives. Using time series data from 1990 to 2022, we analyze the dynamic relationship between GDP per capita, carbon dioxide emissions, deforestation rates, and key green economy indicators, including renewable energy adoption and sustainable agriculture practices. Our findings reveal a modified EKC pattern specific to Nepal's unique geographical and economic context, where the turning point occurs at a lower income level compared to developed nations due to early adoption of green technologies and policies. The results indicate that Nepal's proactive green economy policies, including hydroelectric power development and community forestry programs, have contributed to decoupling economic growth from environmental degradation earlier than predicted by traditional EKC models. The study provides empirical evidence supporting Nepal's green economy transition strategy and offers policy recommendations for sustaining this trajectory while addressing remaining environmental challenges.